2019
DOI: 10.1111/jam.14273
|View full text |Cite
|
Sign up to set email alerts
|

Co‐inoculation ofBacillussp. andPseudomonas putidaat different development stages acts as a biostimulant to promote growth, yield and nutrient uptake of tomato

Abstract: Aims This study builds upon the premise that roots culture distinct bacteria at specific stages of plant growth to benefit of specific microbial services needed at that particular growth stage. Accordingly, we hypothesized that the co‐inoculation of beneficial microbes with distinct properties at specific stages of plant development would enhance plant performance. Methods and Results The chosen microbes were Bacillus pumilus, Bacillus amyloliquefaciens, Bacillus mojavensis and Pseudomonas putida. These microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(69 citation statements)
references
References 55 publications
3
65
0
1
Order By: Relevance
“…However, previous work has found mixed results when using multiple bacteria, often with no stronger effect in plant growth or yield than when one of the strains is inoculated individually. For example, the inoculation of four bacteria (Bacillus pumilus; Bacillus amyloliquefaciens; Bacillus mojavensis; Pseudomonas putida) showed minimal effects on plant growth/yield and even growth/yield reduction when double infections were inoculated (He et al, 2019). Another study on mixtures of Bacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous work has found mixed results when using multiple bacteria, often with no stronger effect in plant growth or yield than when one of the strains is inoculated individually. For example, the inoculation of four bacteria (Bacillus pumilus; Bacillus amyloliquefaciens; Bacillus mojavensis; Pseudomonas putida) showed minimal effects on plant growth/yield and even growth/yield reduction when double infections were inoculated (He et al, 2019). Another study on mixtures of Bacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, root exudates can be substrates, chemotactic or signaling molecules that regulate plant root and microbial interactions [50]. Such plant modulation can be specific to developmental stages [51].…”
Section: Discussionmentioning
confidence: 99%
“…Several metabolic pathways that facilitate growth in plants were overrepresented following application KNU-07 (1.0 × 10 7 cells g −1 soil). He et al [46] reported that rhizobacteria inoculation had beneficial effects on the function of the bacterial community. Predicted metabolic functions related to sporulation and germination were significantly affected during the first week after inoculation with KNU-07 at the highest concentration.…”
Section: Discussionmentioning
confidence: 99%